Association of Shorea leprosula and Shorea johorensis Species with other Species in Tropical Forest - Sari, Nilam; Pratiwi; Yulianti, Mira; Budi Wiati, Catur; Karmilasanti (Media Konservasi, 2024)
Shorea leprosula and Shorea johorensis do not live alone, but are associated with other plant species within a forest ecosystem. The relationships or associations of plants in the forest can be positive and negative. Positive association occurs when a plant species is present together with other plant species, while negative association occurs when a plant species is not present together with other plant species. The purpose of this study was to determine the distribution pattern of tree species, the Important Value Index (IVI), the association between species, and the kinship value of S. leprosula and S. johorensis in the IUPHHK (Timber Forest Product Utilization Business Permit) area of PT. Kemakmuran Berkah Timber, West Kutai Regency, East Kalimantan Province. The results showed that S. leprosula had an IVI (Important Value Index) of 15.89% - 42.02% and S. johorensis had an IVI of 28.56%. Based on the association of kinship values, there was a significant negative association between S. leprosula and Myristica sp. and Cinnamomum sp., with negative coefficients of 7.28% and 8.83%, respectively. As for the S. johorensis species, it was only found in plot 1, with one significant combination with the Palaquium sp. species with a positive coefficient of 5.63%. S. johorensis plays a significant role in plot 1, while S. leprosula shows complex interactions with significant negative species combinations in several plots.